KOMUNIKASI DALAM KURIKULUM MERDEKA : KUNCI SUKSES PEMBELAJARAN MASA DEPAN - Fransisca Wuri Wulandari (EDU RESEARCH, 2024)
Communication is one of the important skills that must be mastered in the future learning era. The Merdeka Curriculum, as one of the innovations in Indonesia's education system, places communication skills as the main focus. This article will examine how communication is accommodated in the Merdeka Curriculum and why this skill is key to successful learning. First, this article will explain the concept of Merdeka Curriculum and the role of communication in it. The Merdeka Curriculum provides freedom for learners to develop themselves according to their interests and talents, so communication skills are vital for expressing ideas, collaborating and solving problems. Furthermore, it will discuss the various components of communication that are integrated, such as oral, written, and digital communication. Then, this article will analyse how Merdeka Curriculum-based learning can hone learners' communication competencies. Various learning models and strategies that encourage interaction, presentation, and discussion will be explained. In addition, authentic and learner-centred assessment will also be discussed as part of efforts to develop communication skills. Finally, this article will conclude the importance of communication in Merdeka Curriculum and its implications for the future of learning. Learners who are proficient in communication will be able to adjust, collaborate, and solve complex problems in the 21st century. Thus, the Merdeka Curriculum can be a solution to produce the next generation who are ready to face global challenges.